Determinants of Share Price in Indonesian Food and Beverage Firms: Faktor-faktor yang Mempengaruhi Harga Saham pada Perusahaan Makanan dan Minuman di Indonesia - Widiyawati , Siska; Biduri, Sarwendah (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Financial statements provide essential information for evaluating company performance and investment decisions in the capital market. Specific Background: In the food and beverage sector, financial ratios such as DER, PBV, and PER are key indicators influencing stock valuation. Gap: Previous studies produced inconsistent findings on the relationships among these ratios and share prices. Aim: This study investigates the roles of Debt to Equity Ratio, Price to Book Value, and Price Earning Ratio in determining share prices of food and beverage companies listed on the Indonesia Stock Exchange during 2016–2018. Results: The findings indicate that Price to Book Value significantly affects stock prices, while Debt to Equity Ratio and Price Earning Ratio show no significant influence. Novelty: The study provides updated empirical evidence from Indonesia’s food and beverage sector. Implications: The results can guide investors in identifying valuation indicators for stock investment decisions. Highlights: PBV significantly predicts share prices in the food and beverage sector. DER and PER show no significant relation to share prices. The findings support valuation-based investment analysis. Keywords: Debt to Equity Ratio, Price to Book Value, Price Earning Ratio, Share Price, Food and Beverage